Quantification of Chlordiazepoxide and Pipenzolate Bromide in Tablets and Comparison with Chromatographic Results - Ozdemir, Abdil; Serkan Keskin, Can (Asian Journal of Chemistry, 2010)
Multiple methods were developed for the quantitative analysis of binary mixture of chlordiazepoxide and pipenzolate bromide in a pharmaceutical preparation. These techniques are categorized into chemometric, graphical and chromatographic methods. Different group of methods were utilized in this study including partial least squares, principle component analysis and classical least squares as chemometric methods, first derivative (DER) as graphical methods and HPLC method as a chromatographic method. In chemometric calculations, UV absorption spectra are taken and without data pretreatment subjected methods were applied. In case of HPLC after proper method development and data treatment, calibration equations were obtained for each active compound. Chromatography was carried out on C-18 column with mobile phase comprising of acetonitrile-methanol (50:50, v/v) pumped at flow rate of 0.8 mL/min. For chromatographic runs, amitriptyline was used as an internal standard in all the samples. The absorbance data was obtained in the range of 200-300 nm for the spectrophotometric studies. Linearity range of all the methods was found to be 8-24 μg/mL for chlordiazepoxide and 4-12 μg/mL for pipenzolate bromide. Mean recoveries were found satisfactory in the range of 95-105 % for both drugs with limit of detection values in the range of 0.14-0.41 μg/mL for each drug. These studies indicated that the significant spectral overlap of the UV-spectra of the drugs showing the need for chemometrics or graphical modeling for simultaneous analysis of the mixtures.